Drosophila melanogaster: A Model System to Study Distinct Genetic Programs in Myoblast Fusion - Pratiti Rout; Mathieu Preußner; Susanne Filiz Önel (Cells, 2022)
Muscle fibers are multinucleated cells that arise during embryogenesis through the fusion of mononucleated myoblasts. Myoblast fusion is a lifelong process that is crucial for the growth and regeneration of muscles. Understanding the molecular mechanism of myoblast fusion may open the way for novel therapies in muscle wasting and weakness. Recent reports in Drosophila and mammals have provided new mechanistic insights into myoblast fusion. In Drosophila, muscle formation occurs twice: during embryogenesis and metamorphosis. A fundamental feature is the formation of a cell–cell communication structure that brings the apposing membranes into close proximity and recruits possible fusogenic proteins. However, genetic studies suggest that myoblast fusion in Drosophila is not a uniform process. The complexity of the players involved in myoblast fusion can be modulated depending on the type of muscle that is formed. In this review, we introduce the different types of multinucleated muscles that form during Drosophila development and provide an overview in advances that have been made to understand the mechanism of myoblast fusion. Finally, we will discuss conceptual frameworks in cell–cell fusion in Drosophila and mammals.